Isolation of Guttiferones from Renewable Parts of Symphonia globulifera by Centrifugal Partition Chromatography - Cottet, Kevin; Fromentin, Yann; Kritsanida, Marina; Grougnet, Raphaël; Odonne, Guillaume; Duplais, Christophe; Michel, Sylvie; Lallemand, Marie-Christine (Planta Medica, 2015)
The aim of this study was to investigate the species Symphonia globulifera, a source of polycyclic polyprenylated acyl phloroglucinols such as guttiferone A, which is known to exhibit a variety of biological activities including noticeable antileishmanial properties. Our goal was the identification and the quantification of guttiferone A in different renewable parts of S. globulifera and its preparative isolation. To the best of our knowledge, there is no data concerning its mechanism of action. Consequently, it is particularly interesting to isolate it in gram quantities in order to establish structure activity relationship studies. After performing high-performance liquid chromatography profiles detecting the presence of guttiferone A and proceeding to its quantification, a centrifugal partition chromatography methodology using a two-phase solvent system of cyclohexane/ethyl acetate/methanol/water (20 : 1 : 20 : 1, v/v/v/v) was applied to each extract. In conclusion, a centrifugal partition chromatography system has been developed to ensure a fast, reliable, and scalable way to isolate, with a high level of purity, guttiferone A from five renewable parts of S. globulifera. Moreover, this methodology can be extended to the isolation of other polycyclic polyprenylated acyl phloroglucinols such as guttiferones B, C, and D.
Keywords: Symphonia globulifera; Clusiaceae; centrifugal partition chromatography; countercurrent chromatography guttiferones; PPAPs